Converting nonsense codons into sense codons by targeted pseudouridylation - Karijolich, John; Yu, Yi-Tao (Nature (London), 2011)
Nonsense codons taken as read The three 'nonsense' or 'stop' codons that signal the ribosome to cease translation — UAA, UAG and UGA — all contain an initial uridine residue. John Karijolich and Yi-Tao Yu demonstrate that isomerization of this uridine, converting it to pseudouridine (Ψ), allows the codons to be read by the ribosome in vivo . Specific amino acids are inserted into the resulting protein, with ΨAA and ΨAG coding for serine and threonine, and ΨGA for tyrosine and phenylalanine. Although there is yet no evidence for a physiological role for this RNA modification, it could offer a way of expanding the genetic code. Similar RNA modification could also be useful as a means of nonsense suppression in vivo , either experimentally or clinically. All three translation termination codons, or nonsense codons, contain a uridine residue at the first position of the codon 1 , 2 , 3 . Here, we demonstrate that pseudouridylation (conversion of uridine into pseudouridine (Ψ), ref. 4 ) of nonsense codons suppresses translation termination both in vitro and in vivo . In vivo targeting of nonsense codons is accomplished by the expression of an H/ACA RNA capable of directing the isomerization of uridine to Ψ within the nonsense codon. Thus, targeted pseudouridylation represents a novel approach for promoting nonsense suppression in vivo . Remarkably, we also show that pseudouridylated nonsense codons code for amino acids with similar properties. Specifically, ΨAA and ΨAG code for serine and threonine, whereas ΨGA codes for tyrosine and phenylalanine, thus suggesting a new mode of decoding. Our results also suggest that RNA modification, as a naturally occurring mechanism, may offer a new way to expand the genetic code.